Green Banking Practices and Percieved Performance of Nepalese Commercial Banks - Chand, Prakash Bahadur; Basnet, Bhabishya; Awasthi, Keshab Raj (PT Mattawang Mediatama Solution, 2025)
The adoption of green banking practices by Nepali commercial banks is examined in this study, with an emphasis on how these policies affect the institutions' perceived performance. A sample of 384 bank employees and seven commercial banks participated in the study, which was carried out in the Kathmandu Valley to gauge their knowledge and opinions of green banking activities. Assessing the degree to which these institutions have adopted green banking practices and their impact on perceived performance is the aim. A structured questionnaire was used to gather data for the descriptive research design, and statistical tools like regression, correlation, mean, and standard deviation were used in the quantitative analysis. The results demonstrate that the majority of staff members are knowledgeable of green banking offerings. Furthermore, the study finds that the perceived performance of banks is positively correlated with green banking components such risk management, green investments, human resource practices, green business strategies, and green products. These programs support larger sustainability objectives in addition to improving the banks' profitability. The study concludes by pointing out that green banking practices boost commercial banks' competitiveness, encourage environmental sustainability, and greatly enhance their performance in Nepal. In order to promote sustainable development and boost operational effectiveness within the Nepalese banking industry, the study highlights the strategic significance of implementing green banking strategies.